Transdermal delivery of narcotic analgesics: pH, anatomical, and subject influences on cutaneous permeability of fentanyl and sufentanil - Roy, S D; Flynn, G L (Pharmaceutical research, 1990)
The permeation of fentanyl and sufentanil through cadaver skin membranes was investigated using in vitro diffusion cell techniques. Neither drug influenced the permeation of the other when they were concurrently applied to the skin membrane. With respect to transdermal delivery, short diffusion lag times of less than 0.5 hr were observed for each compound. Their permeation rates through heat-isolated epidermis and dermatomed (200- to 250-microns) skin sections were essentially the same. However, when the stratum corneum was removed by tape stripping, the respective permeability coefficients were increased greater than 30-fold, establishing the stratum corneum as the principal barrier to their skin permeation. Permeation was also studied as a function of pH. From pH 4 to pH 8 the permeability coefficients of both fentanyl and sufentanil, calculated from the total solution concentration regardless of ionization, increased exponentially. The free base is thus responsible for the relatively facile skin permeation of these drugs. Factoring of the independent permeability coefficients of the ionized and free-base forms was possible, with the latter being over two log orders larger than seen for the protonated species. Permeability coefficients of fentanyl and sufentanil through skin sections obtained from different cadavers varied four- to fivefold. Neither gender nor age was a flux-determining variable for either drug. The permeability coefficients of the drugs through skin sites as diverse as the sole of the foot, chest, thigh, and abdomen were remarkably similar. Their fluxes were sufficient for transdermal administration.